FORMATION OF THE SUSTAINABILITY MODEL OF THE ELECTRIC POWER COMPLEX - A. A. Gibadullin; Yu. V. Yerygin (Вестник СибАДИ, 2018)
Introduction. The article is devoted to the issue of ensuring the stability of the electric power complex in modern Russia.Materials and methods. The conducted research devoted to the capacities condition of the electro power complex shows that the equipment and the basic means on power objects have undergone to moral and physical deterioration. In addition to the state of the main production capacities, the stability of electric power enterprises is influenced by other internal and external factors, among which are organizational and managerial, environmental, production structure and other determinants as well as climatic, geographical, socio-economic conditions, etc. Therefore, the modern electric power complex in the nearest future would not be able to ensure the reliability of electricity supply, which requires the formation of the model to ensure the electricity complex stability.Results. The sustainability could be formed by two components, such as sustainable functioning and sustainable development, which include three fundamental factors: the exports share, the provision of financial resources and the fixed assets state.Discussion and conclusion. The authors concluded that the electric power complex sustainability should be carried out both by increasing the amount of generated electricity, that would be supplied to the world energy markets, and by reducing production costs by updating fixed assets and using innovative technologies.